Inovação tecnológica e práticas pedagógicas: a relação existente entre as tecnologias de informação e comunicação e o professor de língua inglesa da rede estadual de ensino do município de Foz do Iguaçu/PR - Sgorla, Kristian (2016)
Mastering the English Language is a complicated task in Brazil. Reduced study load, overcrowded classrooms, inadequate teacher formation and obsolete teaching material make it common sense to assign this problem to the low quality of public teaching. In addition, there is the conflict between the traditionally proposed way of building knowledge and the contemporary educational paradigm that valorizes the use of Information and Communication Technologies (ICT) in the pedagogical practices. In this scenario, this study intends to find out if the English teachers ally the ICT to their teaching and learning processes in the state of Paraná s Public Education System present in the city of Foz do Iguaçu/PR. In order to do so, it s necessary to locate the context where education and technology meet each other, to understand how this last one enters the school environment. It s also fundamental to know how the implantation and the evolution of English Teaching happened in the Brazilian school curriculum, in order to examine its function in the state public schools. Finally, it s indispensable to know who the teacher of this school subject is and what technological structure the school offers him. For that, the research analyses qualitatively the aforementioned problem. A literature and documentary review gives the theoretical support for the interpretation of the data collected through a questionnaire applied to all the English teachers serving the State s Own Teaching Board and contracted over a Simplified Selective Process, who work with classes between the 6th and 9th years of 28 elementary schools from Paraná s Public Education System present in the city of Foz do Iguaçu/PR, during the school year of 2016. Through this questionnaire, it was found that the school, the teachers and the students are in different technological and language generations. And this, not the cliché of the educators resistance to the use of technologies or the lack of structure of the schools, is what precludes digital teaching practices.